Development and Implementation of a New Model of Care for Patients With Stroke, Acute Hospital Rehabilitation Intensive SErvices: Leveraging a Multidisciplinary Rehabilitation Team. (February 2023) - Langton-Frost, Nicole; Orient, Stephanie; Adeyemo, Jessica; Bahouth, Mona N.; Daley, Kelly; Ye, Bingqing; Lavezza, Annette; Pruski, April
Abstract: The optimal timing and intensity of early rehabilitation remain uncertain. The literature has stated that too early high-intensity mobility within 24 hours can result in poor outcomes as compared with the 24- to 48-hour poststroke ( Stroke 2012;43:2389–94. Stroke 2004;35:1005–9). However, few studies have shown that mobilizing patients a few times per day can have positive results ( Stroke 2004;35:1005–9. Cerebrovasc Dis 2010;29:352–60). In addition to mobility impairments, many patients after stroke have dysphagia, aphasia, and cognitive-linguistic deficits. To date, there is limited literature on early rehabilitation in these areas. Here, we describe a program of enhanced rehabilitation in the acute care hospital. In this enhanced model of care, our team delivers up to six sessions of therapy per day focused on the patient's deficits. A patient can receive up to two sessions of each discipline daily to include physical therapy, occupational therapy, and speech language pathology. The model emphasizes team collaboration between therapy disciplines, physiatry, nursing, and neurology accomplished through a daily therapy schedule, rehabilitation huddle, and direct communication before and after therapy sessions. With this model, we aim to enhance coordination of care resulting in improved patient satisfaction and, ultimately, recovery.